2012
DOI: 10.1002/chem.201203092
|View full text |Cite
|
Sign up to set email alerts
|

7,7,8,8‐Tetraaryl‐o‐quinodimethane Stabilized by Dibenzo Annulation: A Helical π‐Electron System That Exhibits Electrochromic and Unique Chiroptical Properties

Abstract: When two benzene rings are fused to a tetraaryl-o-quinodimethane skeleton, sterically hindered helical molecules 1 acquire a high thermodynamic stability. Because the tetraarylbutadiene subunit contains electron-donating alkoxy groups, 1 undergo reversible two-electron oxidation to 2(2+), which can be isolated as deeply colored stable salts. Intramolecular transfer of the point chirality (e.g., sec-butyl) on the aryl groups to helicity induces a diastereomeric preference in dications 2 b(2+) and 2 c(2+), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Namely, it was shown that covalent assemblies properly incorporating couples of redox-active units can give rise to the formation of a (C sp3 –C sp3 ) carbon–carbon bond that bridges electrochemically active components following a reductive or an oxidative process. For example, typically integrated redox-active chromophoric units are trityliums, ,, heterotricyclic hydrocarbons, , thiophenes, or octamethoxy­tetraphenylene . Of particular interest is the case of bis-acridinium assemblies (e.g., Chart S1a) that are more or less tightly preorganized with various semirigid to rigid scaffolds, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, it was shown that covalent assemblies properly incorporating couples of redox-active units can give rise to the formation of a (C sp3 –C sp3 ) carbon–carbon bond that bridges electrochemically active components following a reductive or an oxidative process. For example, typically integrated redox-active chromophoric units are trityliums, ,, heterotricyclic hydrocarbons, , thiophenes, or octamethoxy­tetraphenylene . Of particular interest is the case of bis-acridinium assemblies (e.g., Chart S1a) that are more or less tightly preorganized with various semirigid to rigid scaffolds, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This result is explained by assuming that the conformational change in dichloromethane is faster than that in benzonitrile. The observed results suggest that 2 could be classified as a dynamic redox system [28–30] . This dynamic redox behavior of 2 could be attributed to the intrinsic electron‐donor ability of TTF inserted in the diphenoquinone moiety.…”
Section: Resultsmentioning
confidence: 86%
“…An interesting method for coupling molecular motions with physical responses in solution is a dynamic redox system . Conformational changes of the π-electronic core due to redox processes affect the electronic nature of the molecule, which results in electrochromic behavior with electrochemical bistability. , For instance, the butterfly-shaped molecular conformation of 11,11,12,12-tetracyanoanthra-9,10-quinodimethane (TCNAQ) in a neutral state was transformed to a planar structure in a dianionic state through two-electron reduction. The CC double-bond character of dicyanomethylene CC(CN) 2 groups in neutral TCNAQ was transformed to C–C single bonds by reduction, which relaxed the steric hindrance between CC(CN) 2 groups and hydrogen atoms of neighboring benzene rings in the dianion state.…”
Section: Introductionmentioning
confidence: 99%